Motivation in Project Management: Systematic Review of the Literature - A. K. Tyulkubayeva; G. B. Nurseiytova; G. S. Sugirova (Экономика: стратегия и практика, 2023)
Motivation plays a critical role in project management as it affects team performance, project success, and organizational outcomes. The purpose of the review: to study the impact of motivation on the effectiveness of the project, to determine the main factors influencing the motivation in project management and the types of motivation of the project team, as well as methods for managing motivation in project activities. The review covered 44 articles published between January 2019 and February 2023 in the Scopus database, Web of Science and Google Scholar. Articles were selected based on their relevance to the topic and analyzed through a predetermined set of criteria. The results obtained show that project management motivation is a complex and multifaceted process that includes various levels of analysis, including individual, team and organizational factors. Project managers should focus on creating a motivating environment for team members to increase project success. Moreover, intrinsic motivation is a better predictor of task performance than extrinsic motivation. The conducted systematic review contributes to the understanding of motivation in project management and provides a basis for further research on this topic. The results of this review have important implications for project managers, who can use this knowledge to motivate team members and improve project success. Moreover, more research is needed on the motivation behind traditional and agile project teams.